2011
DOI: 10.1080/01445340.2011.577145
|View full text |Cite
|
Sign up to set email alerts
|

The Absence of Multiple Universes of Discourse in the 1936 Tarski Consequence-Definition Paper

Abstract: Dedicated to Professor Roberto Torretti, philosopher of science, historian of mathematics, teacher, friend, collaborator-on his eightieth birthday. This paper discusses the history of the confusion and controversies over whether the definition of consequence presented in the 11-page 1936 Tarski consequence-definition paper is based on a monistic fixed-universe framework-like Begriffsschrift and Principia Mathematica. Monistic fixed-universe frameworks, common in pre-WWII logic, keep the range of the individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Etchemendy was not the first to have noticed a major difference between Tarski’s (1936) account and the later model‐theoretic account. Corcoran and Sagüillo (2009) retrace Corcoran’s awareness of the issue since 1964. In a previous draft (2003) of the same article (but without Sagüillo as co‐author), Corcoran claimed that Tarski’s commitment to a fixed‐domain notion of logical consequence was ‘evident’ (in the latest version it is ‘obvious’, (6)).…”
Section: Sher Corcoran Bach Ray Sagüillomentioning
confidence: 99%
See 1 more Smart Citation
“…Etchemendy was not the first to have noticed a major difference between Tarski’s (1936) account and the later model‐theoretic account. Corcoran and Sagüillo (2009) retrace Corcoran’s awareness of the issue since 1964. In a previous draft (2003) of the same article (but without Sagüillo as co‐author), Corcoran claimed that Tarski’s commitment to a fixed‐domain notion of logical consequence was ‘evident’ (in the latest version it is ‘obvious’, (6)).…”
Section: Sher Corcoran Bach Ray Sagüillomentioning
confidence: 99%
“…In addition, fixed‐domain conceptions of consequence were not rare at the time of Tarski’s writing and were in fact upheld by logicians with logicist leanings (Carnap, Ramsey, Russell, Lewis, Langford, etc.) who worked with type theories with a fixed domain of individuals given at the outset (explicit references to such authors are also found, among others, in Gómez‐Torrente 1996 and Corcoran and Sagüillo 2009). Thus, the fixed‐domain conception is not ‘nonstandard’ after all.…”
Section: Counter‐reactions and New Evidence (Bays Mancosu)mentioning
confidence: 99%
“…The debate continued in the 21st century (see [14], [111], [28], [88], [5], [108], [63], [77], [78], [31], [47], [89], [25], [101], and [104]). In the last work the author rejects the standard definition of logical consequence and suggests a sufficiently general form of the consequence relation between abstract signs.…”
Section: Century An Of Mathem Thementioning
confidence: 99%